LINKING JOB SATISFACTION TO EMPLOYEE PERFORMANCE THROUGH ORGANISATIONAL COMMITMENT: EVIDENCE FROM BANK X IN BANDUNG - Augustrianto, Agung; Gunawan, Gunawan (MIMBAR PENDIDIKAN, 2025)
The goal of this study was to look at how a person's job happiness affects their performance at work by employing organisational commitment as a mediating variable among Bank X employees in Bandung. The study was aimed to be explanatory and use quantitative methodologies. Purposive sampling was used to collect data, and questionnaires were delivered to 80 selected respondents. SmartPLS 4 software is used to analyse data using a structural equation (SEM) model. The study's findings show that job satisfaction has a favourable and significant effect on organisational commitment and employee performance. Furthermore, organisational commitment has a major impact on employee performance, and work satisfaction has been shown to moderate the relationship between performance and job satisfaction. These findings indicate that better job satisfaction might boost employee performance and commitment to the business. This study demonstrates that controlling work happiness and strengthening organisational commitment are critical for improving employee performance, particularly in the banking sector.